RUMAH LIMAS: REFLEKSI SEJARAH AKULTURASI KEBUDAYAAN MASYARAKAT SUMATERA SELATAN - Yudi Pratama (Jambura History and Culture Journal, 2019)
Rumah Limas is a from of the local wisdom of the Palembang community, also a a reflection of culture. The concept of the values contained in the local wisdom of the pyramid house means that humans are indirectly connected to the creator. Islamic influence is highly reflected in ornaments, carvings, in the crontuction process, salvation ceremonies carried out during the construction process, the meaning of each room is in the Rumah Limas, and also the concepts of beliefs about construction. These values are a reflection of the norms that are carried out in the life pg the Palembang community who uphold the mores and have a high religious spirit.